Three-Dimensional Assessment of Morphological Changes Following Nasoalveolar Molding Therapy in Cleft Lip and Palate Patients: A Case Report - Edoardo Staderini; Romeo Patini; Andrea Camodeca; Federica Guglielmi; Patrizia Gallenzi (MDPI AG, 2019)
The applications of computer-guided technologies for three-dimensional image analysis provide a unique opportunity to quantify the morphological dimensional changes of the face in a practical and convenient way. Symmetry of the nasolabial area is one of the main factors of facial attractiveness as well as being the main objective of the treatment of cleft lip and palate (CLP). Technological advances in computer-guided visualization modes and their applications to three-dimensional stereophotogrammetry provide more practical opportunities and alternatives for facial analysis. Each study, however, uses different protocols for the acquisition and analysis of three-dimensional images. In addition, each study identifies different anthropometric points and calculates linear and angular measurements with overlapping protocols. Therefore, it is appropriate to define a standardization of the three-dimensional analysis of CLP patients to compare the studies of different research centers. The aim of this report is to propose a protocol to standardize the acquisition and analysis of three-dimensional images to evaluate the three-dimensional changes in the nasolabial area in cleft lip and palate patients undergoing pre-surgical nasoalveolar molding (PNAM).